The Impact of Youth Unemployment Policy - Trine Filges; Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2001)
This paper examines the impact on unemployment, unemployment distribution, wages and welfare of Youth Unemployment Programmes (YUPs). The aim of YUP is to increase the number of young people acquiring skills. We assume that the YUPs are a complete success and consequently analyse what happens when the number of skilled workers increases relatively to the number of unskilled workers. The results depend on the productivity of the skilled workers when employed in the "unskilled sector" relatively to the productivity of the unskilled worker.
hdl:10398/7639
Keywords: J18; J38; J68; 330; Skill; Unemployment; Search